The role of Artificial Intelligence (AI) in the detection and diagnosis of chronic diseases – a review - Zaman, Mumtahina (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2022.